Meta-analysis of fMRI studies related to mathematical creativity - Li, Qingqing; Kim, Sungyeun (Frontiers in Psychology, 2025)
This study presents a comprehensive meta-analysis of fMRI data to explore the neural correlates of mathematical creativity, a vital competence in mathematics education. Utilizing Activation Likelihood Estimation (ALE) and Meta-Analytic Connectivity Modeling (MACM) techniques, we analyzed studies published up to 2022 to identify brain regions activated during mathematical and creative tasks. The findings reveal significant activation in the left inferior frontal gyrus (IFG) and the left superior frontal gyrus (SFG) during both mathematical and creative tasks, emphasizing their roles in idea generation, working memory, and executive control. The MACM analysis further highlights the importance of the frontoparietal network, a key player in cognitive control, for mathematical creativity. This network’s involvement in attention, working memory, and goal orientation aligns with the demands of mathematical problem-solving. Our results offer valuable insights into the neural mechanisms underlying mathematical creativity, providing a foundation for developing targeted educational strategies to enhance this crucial competence in learners.